Importance of leadership styles: a theoretical review approach - Geraldo Campos, Luis Alberto (2020)
The present study describes the importance of leadership styles from a theoretical review approach. The review of theories of leadership styles must be determined from theories of leadership itself, in order to understand this phenomenon in a suitable psychosocial context. This review shows that the theoretical approach to leadership has been approached from various perspectives and what criteria, in turn, have evolved over time, from the beginning of the 20th century to the present day. Understanding this conceptual evolution is the key to achieving an accurate description of leadership styles and knowing their specific applications in organizations. The findings, based on the theory consulted, indicate that the importance of leadership styles lies in the degree of synergy they have, as they care about both the people and the objectives of the led organization; Furthermore, the most important leadership styles are those that guide the conduct of leaders through specific strategies and determined to a limited number of specific cases, that is, a particular type of organization.